1973
DOI: 10.1017/s0017089500001981
|View full text |Cite
|
Sign up to set email alerts
|

The values of a polynomial over a finite field

Abstract: The object of this paper is to derive, using a version of the large sieve for function fields due to J. Johnsen [6], explicit lower boundsfor the average number of distinct values taken by a polynomial over a finite field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…To calculate these multiplicities, we need the following lemma. Particular cases of the lemma were considered in Zsigmondy [25], and in Cohen [5]. The complete result appears in A. Knopfmacher and J. Knopfmacher [8].…”
Section: Resultsmentioning
confidence: 99%
“…To calculate these multiplicities, we need the following lemma. Particular cases of the lemma were considered in Zsigmondy [25], and in Cohen [5]. The complete result appears in A. Knopfmacher and J. Knopfmacher [8].…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that, for lower bounds, there are obvious limits to the results you can expect to obtain -obviously V (f ) ≥ 1 with equality possible, while for polynomials of given degree d, V (f ) ≥ 1 + q−1 d is clear. That said, we have the following deep result by Cohen [2] concerning the average lower bound of V (f ).…”
Section: Polynomials Over Finite Fields and N 2 (F )mentioning
confidence: 74%
“…Results on the average value V(d, 0) of V(f ) when f ranges over all monic polynomials in F q [T ] of degree d with f (0) = 0 were obtained by Uchiyama [24] and improved by Cohen [9]. More precisely, in [9, §2] it is shown that…”
Section: Introductionmentioning
confidence: 99%